Hydrogels based on cashew tree gum and poly(acrylic acid) as potential water suppliers in agriculture - Soares, José Hermeson da Silva (Brazilian Journal of Science, 2022)
Two series of hydrogels called HG1/HG2 consisting of the cashew gum polysaccharide (GC) and polyacrylate poly(acrylic acid) with absorbent capacity and controlled water release, were prepared by polymerization in aqueous solution in the presence of the crosslinking agent N’N’-methylene-bis-acrylamide (MBA) and the reaction initiator potassium persulfate (KPS) under heating and varying the concentration of crosslinker and monomeric. Cashew gum was purified by precipitation in ethanol and studied for parameters of acidity content, conductimetry, yield and macroscopic aspects. Infrared FTIR analysis revelead that GC was modified by insertion into the poly(acrilyc acid) chain, and cross-linking between chains was due to the presence of MBA. The insertion of the GC and the presence of acidic groups gave the polymers absorbent and pH-response properties. In vitro swelling analyzes varying Ph conditions, sal concentration in reversible cycles provided information on degradability through gel phase formation. The degree pf absorption and release simuling application to agricultural soil, showed that hydrogels have application potential as water supply systems, however, the hydrogel with lower monomeric and crosslinking proportions was more promising.